BOOKLET TENTANG PENCEGAHAN OBESITAS TERHADAP TINGKAT PENGETAHUAN PADA SISWA SMP DI KOTA YOGYAKARTA - Astri Praba Shinta; Lutfan Lazuardi; Leny Latifah (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Booklet on Prevention of Obesity on Knowledge Level of Junior High School Students in Yogyakarta CityBackground: Obesity has turned into a global health issue because it occurs nearly everywhere in the world. Prevention of teenage obesity in Special Province of Yogyakarta (DIY) needs to be done as early as possible, especially in the city of Yogyakarta which has the highest rate of obesity compared to other districts, 14,2% within the 5–12 years age group. Behavioural awareness in maintaining their health can be created through an increase in knowledge, which is expected to decrease the obesity rates in teenagers. Objective: This research aims to determine out the effectiveness using booklet (about prevention of obesity) as a medium to educate health towards the level of knowledge. Methods: This type of research is a quasi-experimental with a pre and post-test. Data on knowledge were obtained from pre and post-test questionnaire. Results: There is a difference in the level of knowledge before and after health education using booklet (p<0,05). Booklet gave an effect towards in the form of increased knowledge. Conclusion: There is a difference in the level of knowledge before and after health education using booklet (p<0,05). Booklet gave an effect towards in the form of increased knowledge.